2013
DOI: 10.1590/0103-6440201302158
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Therapy of Extensive Oligodontia: A Case Report

Abstract: Oligodontia is a rare congenital disorder consisting in the absence of six or more teeth. This case report describes a multidisciplinary treatment approach for a 12-year-old male with absence of 11 permanent teeth. Prior to any procedure, all primary teeth were scheduled for extraction due to poor crown-to-root ratio. The treatment plan comprised two phases: 1. orthodontic and speech therapy aimed at overbite and anterior open bite adjustment, as well as tongue position improvement; and 2. prosthetic treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The articulation training from the age of 5 years and 1 month resulted in early improvement of his dysarthria. Gonçalves et al (2013) reported that multidisciplinary treatment, including speech and prosthetic therapy, restores masticatory function and esthetics, allowing the patient to achieve greater self-esteem and better social acceptance [ 23 ]. Thus, we highlight the importance of multidisciplinary collaboration for the treatment of patients with non-syndromic oligodontia.…”
Section: Discussionmentioning
confidence: 99%
“…The articulation training from the age of 5 years and 1 month resulted in early improvement of his dysarthria. Gonçalves et al (2013) reported that multidisciplinary treatment, including speech and prosthetic therapy, restores masticatory function and esthetics, allowing the patient to achieve greater self-esteem and better social acceptance [ 23 ]. Thus, we highlight the importance of multidisciplinary collaboration for the treatment of patients with non-syndromic oligodontia.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment goals are to keep the remaining teeth, recover the masticatory function and aesthetics, improve speech, and reestablish the emotional and psychological wellbeing [ 9 , 11 ]. Regarding the prosthetic treatment, its objectives include restoring the masticatory function, maintaining the position of adjacent natural teeth preventing undesirable movements, such as inclination, extrusion, or migration, improving aesthetics, avoiding social problems to the patient, especially in adolescence, replace the missing teeth without interfering in the growth of the mandible and maxilla [ 24 ]. Considering all possibilities for oral rehabilitation of the referred patient, the prosthetic treatment of choice was the placement of adhesive partial denture due to the difficulty of the patient's adhesion to use a removable appliance.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment goals are to keep the remaining teeth, recover function and esthetics, improve speech, and reestablish the emotional and psychological well-being [2] [49]. Regarding prosthetic treatment its objective include restoring the masticatory function, maintaining the position of adjacent natural teeth, preventing undesirable movements, improving esthetics, avoiding social problems to the patient and replacing the missing teeth without interfering in the growth of the mandible and maxilla [50].…”
Section: )mentioning
confidence: 99%